Suspected NIUAA after indobufen in a patient with ibuprofen allergy: a case report suggesting possible cross-reactivity - Long Luo; Jun Li; Ying Yuan; Ling Zhu (Frontiers in Pharmacology, 2026)
Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used in clinical practice, and hypersensitivity reactions to them are not uncommon. Although ibuprofen and indobufen have different clinical indications, both exert their effects through cyclooxygenase inhibition, suggesting a potential risk of cross-reactivity. This report describes a 52-year-old female patient who experienced pruritus, facial and eyelid edema, tearing, and ocular itching approximately half an hour after two separate exposures to ibuprofen in the past. During the current hospitalization for cerebral infarction, she received indobufen for antiplatelet therapy and developed similar symptoms—eyelid edema, tearing, and pruritus of the head and face—within approximately 10 min. The suspected drug was discontinued and antihistamine therapy was administered, following which the symptoms resolved. Subsequent continued use of other concomitant medications, along with antiplatelet therapy with clopidogrel and cilostazol, did not elicit any allergic reactions; this case suggests indobufen as a possible culprit allergen, and its shared COX-1 inhibitory mechanism with ibuprofen—despite their different chemical groups—raises the possibility of cross-reactive hypersensitivity between the two agents, although this inference remains to be confirmed. Although allergic reactions to indobufen are rare in clinical practice, clinicians should remain vigilant about the potential risk of cross-reactivity when prescribing indobufen to patients with a history of NSAID hypersensitivity.